Cocoa Bean Extract Impact on the Number of Osteoblast and Osteoclast in Orthodontic Teeth Movement - Rudy Joelijanto; Rina Sutjiati; Sulistiyani Sulistiyani; Sayidah Khadijah; Fitri Arida Sabhatina (Humanistic Network for Science and Technology (HNST), 2022)
In orthodontic therapy, mechanical force produces remodeling. Because the process of bone resorption on tooth movement is larger than that of bone apposition when a normal force is applied, a balance is required by increasing the number of osteoblasts and lowering the number of osteoclasts. The purpose of this study was to look at the ability of cocoa bean extract to assist balance the apposition and resorption of alveolar bone during orthodontic tooth movement. A total of 36 male Wistar rats were separated into three groups of Group K-(untreated rats), K+ (giving an orthodontic mechanical force), and P (giving an orthodontic mechanical force and a dosage of 250 mg/kg BW cocoa bean extract). Following euthanasia at 7 and 14 days of therapy and osteoblasts and osteoclasts were counted. The results showed that there was an increase in osteoblasts number and a decrease in osteoclasts number in the treatment group, as indicated by the results of calculating the average number of cells in each group, which were supported by statistical tests using SPSS, which revealed significant differences between groups. In orthodontic tooth movement, cocoa bean extract has the ability to enhance the number of osteoblasts while decreasing the number of osteoclasts. Keywords: osteoblasts; osteoclasts; orthodontic tooth movement; cocoa bean extract